Implementasi Smart City di Jakarta: Problematika Keamanan Privasi dalam E-Governance pada Digitalisasi Transaksi JakLingko - Chasya Nabila; Naila Azaria Arumi; Nova Jojor; Fatkhuri Fatkhuri; Maisarah Mitra Adrian (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
The development of e-government within the smart city framework has encouraged local governments to provide more integrated digital public services, including Jakarta’s transportation system through JakLingko. The integration of cashless payments across TransJakarta, MRT, LRT, and Mikrotrans has improved mobility efficiency and convenience through electronic cards and digital applications. However, alongside these benefits, privacy and security concerns have increasingly emerged in everyday use. Open visibility of balance information during tap-in transactions, dependence on assistance in crowded spaces, and risks such as card swapping reveal vulnerabilities within the system that may influence public perceptions of government digital services. This study applies a descriptive qualitative approach using trust in e-government theory to examine how privacy security issues affect public trust in JakLingko. The findings indicate that digital transformation alone does not automatically generate trust through efficiency or technological integration. Public trust is shaped by whether users feel secure, protected, and free from vulnerability during transactions. The study also shows that continued service use does not always reflect genuine trust, as users may rely on JakLingko due to limited alternatives. Therefore, successful e-government implementation should emphasize not only efficiency and technological advancement but also stronger privacy protection and user security.